2017
DOI: 10.1371/journal.pone.0183195
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in pulmonary tuberculosis cases in Puducherry and Tamil Nadu, India: Opportunities for intervention

Abstract: BackgroundWe aimed to define characteristics of TB patients in Puducherry and two districts of Tamil Nadu, India and calculate the population attributable fractions (PAF) of TB from malnutrition and alcohol.MethodsNew smear-positive TB cases were enrolled into the Regional Prospective Observational Research for Tuberculosis (RePORT India) cohort. Census and National Family Health Survey data were used for comparisons.ResultsData were analyzed for 409 participants enrolled between May 2014-June 2016; 307 (75.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…This is in accordance with global and Hajj-related data and established risk factors for TB [1,7,10,12]. However, the prevalence of coexisting chronic diseases (63%, 17/27) among TB patients, especially diabetes, was higher than that reported internationally as well as previous studies among Hajj pilgrims with TB [7,[12][13][14]. The presence of chronic diseases, increases the risk of TB disease, predisposes to severe illness and complicates TB treatment [1,12].…”
Section: Discussionsupporting
confidence: 87%
“…This is in accordance with global and Hajj-related data and established risk factors for TB [1,7,10,12]. However, the prevalence of coexisting chronic diseases (63%, 17/27) among TB patients, especially diabetes, was higher than that reported internationally as well as previous studies among Hajj pilgrims with TB [7,[12][13][14]. The presence of chronic diseases, increases the risk of TB disease, predisposes to severe illness and complicates TB treatment [1,12].…”
Section: Discussionsupporting
confidence: 87%
“…This is a cross-sectional analysis of data from a cohort study under Regional Prospective Observational Research for Tuberculosis (RePORT) India Consortium. Details of the study design have been previously reported 11–14…”
Section: Methodsmentioning
confidence: 99%
“…Only newly diagnosed smear-positive and culture-positive pulmonary TB cases were included. Details on data collection and procedures were previously reported 11–14…”
Section: Methodsmentioning
confidence: 99%
“…5 We see this play out in India where the Population Attributable Fraction (PAF) of TB due to malnutrition in India can be as high as 61.5% in women and 57.4% in men. 6 The impaired cell-mediated immunity in individuals with severe malnutrition affects the ability to control the infection and increases likelihood of progression to TB disease. 7,8 Not only does undernutrition increase the risk for TB, it also increases the severity of disease.…”
Section: Undernutrition: Scale Of Problemmentioning
confidence: 99%